The impact of cultural values on Vietnamese ethnic entrepreneurs in Germany - Quynh Duong Phuong; Aki Harima (Journal of Entrepreneurship, Management and Innovation)
While culture plays a central role in ethnic entrepreneurship, extant research offers a limited understanding of this aspect. This paper investigates the impact of cultural values on Vietnamese ethnic entrepreneurs in Germany. We conducted five case studies with Vietnamese ethnic entrepreneurs. Based on the case studies, we identified four distinct types of cultural values that have a crucial impact on the entrepreneurial activities of the observed Vietnamese entrepreneurs in Germany: i) Family involvement, ii) Cautiousness in entrepreneurial decision-making, iii) Assertiveness in front of the community and iv) Cordiality of service. The study offers an initial insight into the role of cultural values in entrepreneurial decision-making processes of ethnic entrepreneurs and recognizes a reciprocal effect between cultural values and the balance of embeddedness.